Amplifying weak signals: a method-building approach for inclusive climate resilience strategy making - Champlin, Carissa; Eapen, Ann; Vitkutė, Rūta; Groot, Janne; Forgaci, Claudiu (Frontiers in Computer Science, 2024)
Socio-ecological inclusion and the impacts of climate change on the built environment are two shared concerns central to the design and planning of the just transition in cities. The just transition leans heavily on inclusive convergence processes that are grounded in knowledge integration and transdisciplinary practice. However, there is a paucity of effective methods for the inclusion of so-called weak signals from actors situated at the periphery of these convergence processes.Building on the concept of structured flexibility, we introduce a building-blocks approach as a modular architecture for constructing methods for distributed engagement and knowledge integration beyond conventional small-group settings. By engaging in research through design, the Amplifying Weak Signals approach was prototyped with students in the context of dealing with heatwaves in The Hague and tested with expert users from the region who facilitate resilience strategy-making processes. Out of 900 possible building block combinations, 18 methods were created during prototyping. The resulting heatwave strategies that were drafted based on the collected peripheral knowledge showed the integration of new socio-ecological issues rather than a drastic departure from the baseline resilience strategy of the city. We discuss the research findings and their use in the production of guidelines for the construction of methods to integrate peripheral knowledge in convergence processes. Ongoing work to develop the guidelines in the form of an open-access, interactive repository of knowledge elicitation methods for urban resilience spatial planning will also be described. Recommendations for scaling the approach are provided.